Constituents of carbazole alkaloids and anti-cancer properties of extracts, mahanine, isomahanine, mahanimbine, and girinimbine from Bergera koenigii - Eric Wei Chiang Chan, Siu Kuin Wong (Journal of Applied Pharmaceutical Science, 2024)
The new name of Murraya koenigii (L.) Spreng. is Bergera koenigii L., the Indian curry leaf tree. Constituents of carbazole alkaloids from different plant parts of B. koenigii are compiled. Based on the number of reports, mahanimbine (MNB) and koenimbine are the two most dominant carbazole alkaloids from the leaf of B. koenigii. Carbazole alkaloids selected for review are mahanine (MN), isomahanine (IMN), MNB, and girinimbine (GNB) which are pyranocarbazoles as they possess the pyranocarbazole skeleton. MN, IMN, and MNB have 23 carbons and four methyl groups, while GNB has 18 carbons and three methyl groups. The anti-cancer properties of extracts and carbazole alkaloids from B. koenigii are tabulated with information on cancer types, cancer cell lines, effects, and mechanisms. Other pharmacological properties are briefly mentioned. Findings on the anti-cancer properties of extracts and carbazole alkaloids that will generate interest for further research are included as concluding remarks. Eight areas for future research were suggested.
Keywords: Murraya koenigii, Rutaceae, Indian curry leaf, pyranocarbazoles